2016
DOI: 10.1038/ncomms11646
|View full text |Cite
|
Sign up to set email alerts
|

klf2a couples mechanotransduction and zebrafish valve morphogenesis through fibronectin synthesis

Abstract: The heartbeat and blood flow signal to endocardial cell progenitors through mechanosensitive proteins that modulate the genetic program controlling heart valve morphogenesis. To date, the mechanism by which mechanical forces coordinate tissue morphogenesis is poorly understood. Here we use high-resolution imaging to uncover the coordinated cell behaviours leading to heart valve formation. We find that heart valves originate from progenitors located in the ventricle and atrium that generate the valve leaflets t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
169
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 101 publications
(181 citation statements)
references
References 66 publications
(109 reference statements)
4
169
0
Order By: Relevance
“…A remarkable finding in our gene expression studies was the lack of any change in Nfatc1 , a gene expressed by endocardial cells that is known to play a critical role in cushion remodeling similar to that observed for KLF2 (Chang et al, 2004), and a lack of change in expression of Trpv4 , Pkd2 ( Trpp2 ) or Fn1 (Figure S5), genes previously associated with klf2a function in the developing zebrafish heart valve (Heckel et al, 2015; Steed et al, 2016). To further investigate potential regulation of NFATC1 by KLF2 we stained Nfatc1 Klf2 KO and control cushions with anti-NFATC1 antibodies.…”
Section: Resultssupporting
confidence: 72%
See 4 more Smart Citations
“…A remarkable finding in our gene expression studies was the lack of any change in Nfatc1 , a gene expressed by endocardial cells that is known to play a critical role in cushion remodeling similar to that observed for KLF2 (Chang et al, 2004), and a lack of change in expression of Trpv4 , Pkd2 ( Trpp2 ) or Fn1 (Figure S5), genes previously associated with klf2a function in the developing zebrafish heart valve (Heckel et al, 2015; Steed et al, 2016). To further investigate potential regulation of NFATC1 by KLF2 we stained Nfatc1 Klf2 KO and control cushions with anti-NFATC1 antibodies.…”
Section: Resultssupporting
confidence: 72%
“…Moreover, confocal analysis demonstrated co-expression of wnt9b and klf2a by individual endocardial cells at these sites (Figure 7B, C). Prior studies have demonstrated that klf2a expression in the endocardial cells overlying the developing AV valve is strictly dependent upon blood flow and hemodynamic shear forces (Heckel et al, 2015; Steed et al, 2016; Vermot et al, 2009). As previously shown for klf2a , wnt9b expression was extinguished or severely reduced in the hearts of silent heart ( tnnt2a ) mutant fish that lack blood flow (Sehnert et al, 2002) (Figure 7D, E).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations